Characterization and Functional Product Development from Bael (Aegle marmelos L. Correa) Fruit Pulp. Issue 4 (20th November 2015) - Asghar, Nosheen; Imran, Muhammad; Mushtaq, Zarina; Ahmad, Rabia Shabir; Khan, Muhammad Kamran; Ahmad, Nazir; Ahmad, Uswa
Abstract: The present study adds value to bael fruit pulp by using it in jam production. The functional jams were prepared as T0 (100% apple pulp), T1 (75% apple : 25% bael), T2 (50% apple : 50% bael), T3 (25% apple : 75% bael) and T4 (100% bael pulp), respectively. Results showed that bael pulp was richer in dietary fiber contents while apple pulp showed higher sugar and bioactive compounds before jam production. Decrease in moisture, nonreducing sugars and pH while increase in acidity, total soluble and reducing sugars ( P  ≤ 0.05) were observed with nonsignificant changes in dietary fiber for treatments during storage ( P  ≥ 0.05). The jam processing significantly decreased the vitamin C and phenolic contents ( P  ≤ 0.05). Maximum decrease of vitamin C (53%) and total phenolic content (75%) was found for T0, respectively. The lowest concentration of bioactive compounds in treatments was noted after 60 days of storage. Overall, the jam samples of T2 presented a higher sensory acceptability. Practical Applications: The results from this work revealed essential information that could promote the commercialization of bael fruit for the development of functional products for discerning consumers. Moreover, the results from this study will aid in the formulation of more healthy and nutraceutical products that may address a critical industrial demand in terms of formulation options for fruits. Additional studies should be undertaken to determine the maximal shelf life of products supplemented with bael fruit and treatment of nutritional disorders through their absorption, metabolism and distribution pattern into biological tissues.